EFFECTIVE USAGE OF SYNONYMS IN EXPRESSING OUR THOUGHTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In this article the usage and importance of English synonyms will be discussed and explained them through examples.